The effects of obesity on the life activity and self-esteem of the elderly - Ewelina Szkutnicka; Marzena Samardakiewicz; Agnieszka Barańska; Anna Sokołowska; Ewelina Firlej; Hubert Szkutnicki (Kazimierz Wielki University, 2018)
Introduction. Metabolic disorders, the coexistence of many diseases, lack of physical activity, bad nutrition and low economic status are factors which increase the risk of being overweight of obese.  We are currently witnessing an increase in obesity along with age, which has been intensifying in recent years. Aim of the paper. The aim of the paper was to analyse the influence of overweight and obesity among the elderly on their life activity, level of self-esteem and satisfaction with life. Material and methods. The research was carried out on October 2017 in Opole Lubelskie (in Lubelskie Province). The study group consisted of 50 people aged over 65. The selection criteria for respondents were age (> 65) and BMI (>25). A specially prepared questionnaire was used for the research. The BMI of the respondents was calculated from measures of their height and body mass. Results. The BMI calculated confirmed class I obesity among 28.57% of women and 18.19% of men, class II obesity in 39.29% of women and 36.36% of men and class III obesity in 32.14% of women and 45.45% of men (Graph 1). 78% of respondents assessed their lifestyle as not very active. A whole 92% are not satisfied with their appearance. All those surveyed believe they are perceived badly by other people. Conclusions. Obesity has a major influence on the quality of life of people of advanced age.  Excessive body mass has a detrimental effect on self-esteem and can lead to the elderly withdrawing from social life. Key words: obesity, elderly, self-esteem, life satisfaction